Blood HDAC4 Variation Links With Disease Activity and Response to Tumor Necrosis Factor Inhibitor and Regulates CD4+ T Cell Differentiation in Ankylosing Spondylitis - Dou, Bin; Ma, Fuzhe; Jiang, Zhenyu; Zhao, Ling (Frontiers in Medicine, 2022)
Purpose Histone deacetylase 4 (HDAC4) regulates the progression of autoimmune diseases. This study aimed to further investigate the correlation between HDAC4 and Th cells, inflammation, disease activity, and treatment response in patients with ankylosing spondylitis (AS). Methods A total of 132 active patients with AS were enrolled, of whom 54 patients received TNF inhibitor (TNFi) and 78 patients received NSAID. Serum HDAC4 was measured by ELISA in patients with AS before treatment (W0) and at week (W)4, W8, and W12 after treatment. Meanwhile, serum HDAC4 was detected in 30 patients with osteoarthritis and in 30 healthy controls (HCs) by ELISA. Besides, naïve CD4+ T cells from patients with AS were isolated, followed by modulation of HDAC4 and then polarization toward Th1, Th2, and Th17. Results Histone deacetylase 4 was reduced in patients with AS compared with HCs and patients with osteoarthritis (both P < 0.01). In patients with AS, HDAC4 was negatively correlated with TNF (P < 0.001), IL-1β (P = 0.003), Th17 proportion (P = 0.008), C-reactive protein (P < 0.001), and ASDAS (P = 0.038), but not with IL-6, Th1 proportion, or other characteristics. Meanwhile, HDAC4 increased from W0 to W12 (P < 0.001); HDAC4 at W8 (P = 0.014) and W12 (P = 0.006) was raised in ASAS40-response patients than ASAS40-non-response patients; further subgroup analysis showed that HDAC4 at W12 was higher in ASAS40-response patients than ASAS40-non-response patients (P = 0.016) in the TNFi-treated group, but not in the NSAID-treated group. In addition, HDAC4 negatively regulated the polarization of naïve CD4+ T cells toward Th17 (P < 0.01), but not Th1 or Th2. Conclusion Histone deacetylase 4 is associated with lower inflammation, and the disease activity negatively regulates Th17 polarization, whose increment after treatment reflects favorable outcomes in patients with AS.